The Effect of E-WOM, Ease of Use and Trust on Purchase Decisions (Study on Tokopedia Application Users) - Badir, Mailal; Andjarwati, Anik Lestari (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2020)
The purpose of this study is to determine the effect of e-WOM, convenience, and trust in purchasing decisions. The development of internet-based trading systems or e-commerce changes the patterns of consumer behavior from conventional shopping to shopping digitally or online. The sample in this study was 200 respondents of Tokopedia users. The analyis uses multiple regression analysis. The results showed there was no significant effect of the e-WOM variable on purchasing decisions, and there was a substantial influence on the easiness and trust variables on buying decisions.